THE FACE BEHIND THE ZOOM: WHAT MATTERS? - Emanuel Sunarto (International Journal of Humanity Studies (IJHS), 2022)
Since Covid-19 pandemic, Zoom has been adopted by many as an online platform to facilitate learning. This article addresses students’ (dis)agreement to how they perceive their faces in Zoom; whether it is technically a matter of either on-or-off video mode; of insecurities, of any psychological impacts, and of the notion of face as good name or reputation. A survey by means of Google form was organized in the last two meetings of two courses in the odd semester of academic year 2021-2022 to elicit students’ responses to any of Likert-based five scales of (dis)agreements to 16 statements concerning face in Zoom. 122 ELESP USD students of the third and fifth semester responded to this survey. Data were analyzied and interpreted by means of percentage of agreements. The findings reveal that the notion of face in Zoom is initially and in majority agreed as a matter of being in either on-or-off video mode which depends on the stability of internet connection. Next, being in on-or-off video mode is largely bound to whether there is any obligation to be so. The majority agree also that not showing face in Zoom allows them to do side work apart, and prevents matters of privacy from being exposed. The majority also agree that one’s face in Zoom reflects psychological aspects such self pride and honor, dignity, consideration, tact, poise, and perceptiveness. Preference to being on-or-off-video mode is also a matter of not exposing one’s state of insecurities, and is concerned with the notion of face as a representation and approval of self reputation or good name.